Some Criticism of the Tobin Tax - Markus Haberer (University of Konstanz, Center of Finance and Econometrics (CoFE), 2003)
High volatility and enormous international capital flows are negative effects of the globalization of financial markets that can lead to financial crises like those of the 1990s. The Tobin tax often has been put forward as a measure to diminish globalization risks since it is claimed to discourage short-term speculation. The arguments of the proponents of this transactions tax are based on the assumption that (i) short-term trading is destabilizing and speculative and causes the volatility to increase, (ii) the Tobin tax does discourage this speculation and (iii) the Tobin tax causes market participants to orientate more by macroeconomic fundamentals. This paper suggests that these assumptions are quite questionable. Moreover, a Tobin tax of a sensible rate would be too small to protect countries from currency fires and would generate only little monetary autonomy. In addition to theoretical economic doubts there arise some political problems, which can make the tax to become infeasible.
urn:nbn:de:bsz:352-opus-9787
Keywords: 330; Globalization; International Financial Markets; Tobin Tax; Transactions Tax; Tobinsteuer; Kritik